Anticancer effects of limonene and phosphatidylinositol 3- Kinase (pi3k) inhibitor combination in colon cancer cell lines - Y. RAJA RATNA REDDY; MANISHA SINGH; VASANTI KABRA; P. CHANDRA SEKHAR; K. SREEJA VAMSI; B. RAMACHANDRA REDDY; C. DAMODAR REDDY (International Journal of Pharma and Bio Sciences, 2017)
Aberrant activation of phosphotidylinositol 3-kinase (PI3K) pathway effectors has been observed in many cancers including colorectal cancer. As cancers develop due to multiple genetic alterations it is seldom possible to treat them with monotherapy. So, combination therapy has been the standard care in cancer treatment. Therefore, the anticancer effects of the combination of limonene which is a natural monoterpene and NVP-BEZ235, a dual inhibitor of PI3K/mammalian target of rapamycin (mTOR) pathway were investigated in colorectal cancer cell lines. In vitro anticancer assays such as cell viability, cell cycle analysis, apoptosis, caspases estimation and Western blot analysis were performed to determine the combination effects on cells. Results showed that both drugs exhibited dose and time dependent cytotoxicity. Drug combination significantly decreased the phosphorylation of p-70S6K, p-AKTSer473andp-AKTThr308. The inhibition of p-70S6K phosphorylation was more sensitive than p-AKTSer473. Disruption of the known S6K1-IRS-1 negative feedback loop may possibly explain the reversal of p-AKT after 48h treatment with either of the drugs alone. However, the combination of limonene and BEZ may help to alleviate the negative feedback activation of PI3K signaling. This combination also induced G1 phase arrest in the cells and increased the expression of Bcl-2 family mediated apoptosis markers. In conclusion, the results indicate that limonene and BEZ combination demonstrated anticancer effects and are mediated by down regulation of PI3K/mTOR signaling and induction of apoptosis by mitochondrial death pathway.